Polluter identification with spaceborne radar imagery, AIS and forward drift modeling. Issue 2 (30th December 2015) - Longépé, N.; Mouche, A.A.; Goacolou, M.; Granier, N.; Carrere, L.; Lebras, J.Y.; Lozach, P.; Besnard, S.
Abstract: This study defines and assesses a new operational concept to identify the origin of pollution at sea, based on Synthetic Aperture Radar, Automatic Identification System, and a forward drift model. As opposed to traditional methodologies where the SAR detected pollution is backtracked in the past, our approach assumes that all the vessels pollute all along their way. Based on all the AIS data flows, the forward-tracked simulated pollutions are then compared to the detected pollution, and the potential polluter can be finally identified. Case studies are presented to showcase its usefulness in a variety of maritime situations with a focus on orphan pollutions in a dense traffic area. Out of the identification of the suspected polluters, the age and eventually the type of the pollution can be retrieved. Highlights: Integrated system for polluter identification based on AIS, SAR and drift modeling First-ever use of the forward-track approach (as far as our knowledge goes) Proven usefulness with case studies, soon operational in CleanSeaNet services Comprehensive discussion on system's limitations and future improvements